Knowledge of pre-marital genetic screening among students of osun state polytechnics in nigeria (2011)
This study investigated the inhibitors to recreational sport participation among academic staff in Osun State College of Education, Ua-Orangun, Nigeria. The population for the study consisted of all academic staff of Osun State College of Education, lla-Orangun out of which a total of 157 respondents were selected through purposive and maximum variation sampling technique from 5 schools that were randomly selected. Three hypotheses on the effect of participation in recreational sports on Health Status were tested, and all were found significant after subjecting them to chi-square analysis at 0.05 level of significance. Based on the findings of this study it was concluded that job demand, lack of motivation and erroneous belief are some of the inhibitors to recreational sport participation among academic staff in Osun State College of Education, Ua-Orangun. It was therefore recommended that the college management should carry out. a comprehensive auditing of the academic staff work load with the aim of reducing it. Keywords: Inhibitors, recreational sport, healthcare, academic staff